Creativity in higher education: the impact of classroom debate on the academic performance of administrative science students / Azlyn Ahmad Zawawi, Junaida Ismail and Irwana Nooridayu Muhamad Hakimi - Ahmad Zawawi, Azlyn; Ismail, Junaida; Muhamad Hakimi, Irwana Nooridayu (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
Classroom debate has been widely used as a learning method especially at the secondary and tertiary level. Classroom debate enhances self-confidence, critical thinking, analytical capabilities, communication skills, and teamwork. Although studies involving the impact of classroom debate has vastly been done in the context of learning the second language, psychology, philosophy, and pure science; specific studies that focus on administrative science field are still scarce. Administrative science subjects are multidisciplinary, critical and analytical, and mostly it covers aspects of administrative concepts, management principles and practices, administrative and management theories, public sector management, and international relations. Classroom debate are beneficial and relevant to be applied in administrative science subjects as a properly orchestrated debate can allow students to exert fresh ideas and develop reasoning skills that can improve their academic performance. Therefore, this paper aims to establish a conceptual review on the impact of classroom debate on students' academic performance within the context of higher education, particularly in the administrative science field. A conceptual framework is subsequently proposed linking the benefits of classroom debate with students' academic performance.